National Athletic Trainers' Association Position Statement: Preventing Sudden Death in Sports - Casa, Douglas J. (The National Athletic Trainers' Association, Inc, 2012)
OBJECTIVE: To present recommendations for the prevention and screening, recognition, and treatment of the most common conditions resulting in sudden death in organized sports. BACKGROUND: Cardiac conditions, head injuries, neck injuries, exertional heat stroke, exertional sickling, asthma, and other factors (eg, lightning, diabetes) are the most common causes of death in athletes. RECOMMENDATIONS: These guidelines are intended to provide relevant information on preventing sudden death in sports and to give specific recommendations for certified athletic trainers and others participating in athletic health care.